Effects of online cognitive behavioral therapy on depression, negative automatic thoughts, and quality of life in Thai university students during the COVID-19 lockdown in 2021: a quasi-experimental study - Prasartpornsirichoke, Jirada; Pityaratstian, Nuttorn; Poolvoralaks, Chayanit; Sermruttanawisith, Nusaba; Polpakdee, Kornsiri; Pholphet, Kwunkao; Buathong, Napakkawat (Frontiers in Psychiatry, 2025)
BackgroundThe COVID-19 pandemic significantly affected university students’ mental health, family socioeconomic conditions, and social relationships, contributing to increased depression. In Thailand, strict lockdowns and social distancing limited access to in-person psychotherapy.AimThe aim of this quasi-experimental single-group study was to investigate the impact of online cognitive behavioral therapy (online CBT) on depressive symptoms, negative automatic thoughts, and quality of life in Thai university students with moderate to severe depression during the 2021 COVID-19 lockdown.MethodsSeventy Thai university students aged 18–25 participated. Self-reported outcomes were assessed using the Beck Depression Inventory (BDI-IA), the Revised Automatic Thoughts Questionnaire (ATQ-RP), and the WHO Quality of Life-BREF (WHOQOL-BREF-THAI). A mixed-effects model was used to analyze the impact of online CBT at a significance level of 0.05.ResultsOnly 33 successfully finished all 12 online CBT sessions and the follow-up assessment. This indicates a dropout rate of 52.9%. The findings revealed a negative linear correlation between the number of CBT sessions and both depressed symptoms and negative automatic thoughts. On the other hand, we observed a positive linear association with quality of life. At the beginning of the study, the mean scores for depressive symptoms significantly decreased from 27.84 (95% CI: 25.56-30.13) to 11.47 (95% CI: 8.54-14.40) at the twelfth session and further declined to 9.43 (95% CI: 6.41-12.46) during the follow-up period. Similarly, the mean scores of negative automatic thoughts decreased from 20.81 (95% CI: 19.08-22.55) to 10.46 (95% CI: 7.96-12.96) and 9.38 (95% CI: 6.77-11.99) respectively. On the other hand, the mean scores for quality of life increased from 69.73 (95% CI: 66.88-72.58) to 85.37 (95% CI: 80.83-89.90) and 85.61(95% CI: 80.84-90.38) consecutively.ConclusionsThis study provides evidence that the implementation of online cognitive behavioral therapy leads to a significant reduction in depression symptoms and negative automatic thoughts, as well as an improvement in the quality of life among Thai university students during the COVID-19 lockdown. The results highlight the benefits and availability of online cognitive behavioral therapy as a mental health intervention during challenging times and in geographically isolated regions.Clinical trial registrationhttps://www.thaiclinicaltrials.org/ identifier, TCTR20210310002.